2015
DOI: 10.1186/s12995-015-0049-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hematological, biochemical effects and genotoxicity among pesticide sprayers in grape garden

Abstract: Background: Many studies revealed toxic effects of pesticides on pesticide handlers but very fewer studies have been reported among grape garden pesticide sprayers in India. The purpose of this study was to evaluate the effect of pesticides among grape garden sprayers. Methods: 27 pesticide sprayers in study group and 27 non sprayers in control group were recruited. Blood samples were analyzed for hematological profile, biochemical parameters and urine samples for oxidative stress, buccal mucosal cells for gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 16 publications
4
22
0
1
Order By: Relevance
“…Results from the current report regarding pesticide use and hematological parameters are consistent with previous studies which failed to reveal a consistent relationship between pesticide exposure and hematological parameters among farmers 21,27,28 . Thus, a Thai study with orchid farmers found no significant differences in hematological parameters between subjects highly exposed to pesticides and non-exposed subjects 21 .…”
Section: Pesticide Use and Hematological Parameterssupporting
confidence: 90%
“…Results from the current report regarding pesticide use and hematological parameters are consistent with previous studies which failed to reveal a consistent relationship between pesticide exposure and hematological parameters among farmers 21,27,28 . Thus, a Thai study with orchid farmers found no significant differences in hematological parameters between subjects highly exposed to pesticides and non-exposed subjects 21 .…”
Section: Pesticide Use and Hematological Parameterssupporting
confidence: 90%
“…After DDT absorption, it is distributed to all organs and a portion will be stored in fatty tissues, especially if the exposure was massive [141][142][143][144][145][146] . Many insecticides, including DDT, were reported to be responsible for leading the development of HCC [147][148][149][150][151][152] .…”
Section: Pesticidesmentioning
confidence: 99%
“…Toxicity depends on the compound family, and is generally greater for the older compounds. In humans, pesticides are responsible for acute poisonings, as well as long-term health effects, including cancer and adverse effects on reproduction (78,79,190). …”
Section: Resultsmentioning
confidence: 99%